Feminist Dating App Perspective: Unveiling Indonesian Women's Dating Fantasy on Bumble - Marco, Anastasia Cindy; Puspita, Virienia; Abrahams, Farell Giovan (CV. Creative Tugu Pena, 2024)
This study delves into the intricate relationship between Bumble, a feminist-oriented dating app, and the perception of its community, both online and offline. Bumble's unique feature, which empowers women to initiate conversations in heterosexual matches, challenges entrenched gender norms prevailing in conventional dating platforms like Tinder. Beyond the innovative app design, the research employs the symbolic convergence theory to dissect shared fantasy themes, chains, and types within their community, unraveling how these dramatized messages contribute to empathetic communication and foster a sense of community. In addition to scrutinizing user narratives, the study aims to bridge the symbolic convergence observed on Twitter with the tangible experiences of women navigating Bumble's feminist features in the real world. This comprehensive exploration not only sheds light on the symbiotic relationship between online communities and the dynamics of feminist-driven dating apps but also contributes valuable insights to the broader discourse on the impact of technology on societal norms and interpersonal relationships. The research seeks to offer a nuanced perspective that goes beyond the digital realm, encompassing the multifaceted ways in which technology influences and reflects the evolving landscape of gender dynamics in contemporary society. Keywords: Online Dating, Fantasy Chain, Fantasy Theme, Symbolic Convergence Theory, Feminist Dating App